2017
DOI: 10.1002/lary.26961
|View full text |Cite
|
Sign up to set email alerts
|

Could laser‐assisted dissection of the pre‐epiglottic space affect functional outcome after ESL?

Abstract: 4. Laryngoscope, 128:1371-1378, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…21,22 Regarding functional outcomes, Bertolin et al, found worse results in patients undergoing endoscopic epiglottis and PES resection compared to patients undergoing the same resection by open approach reported to the increase in the sphincter capacity potentially obtained by a compensatory effect of the laryngopexy performed in open surgery, advocating for the authors for open surgery in every case requiring resection of the epiglottis and the PES. 23 In elderly patients over 65 years old specifically, Chiesa Estomba et al reported postoperative rates of aspiration pneumonia of 20% after open surgery and of 41.2% after TLM in supraglottic carcinoma, albeit difference was not statistically significant and the rates of dysphagia were similar, 30% versus 29.4%, respectively. 9 Together with our results, these findings argue for considering a transoral procedure rather than an open procedure for a tumor smaller than thirty millimeters when local exposition is favorable and no local extension associated with a risk of decreased local control after a transoral is suspected.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…21,22 Regarding functional outcomes, Bertolin et al, found worse results in patients undergoing endoscopic epiglottis and PES resection compared to patients undergoing the same resection by open approach reported to the increase in the sphincter capacity potentially obtained by a compensatory effect of the laryngopexy performed in open surgery, advocating for the authors for open surgery in every case requiring resection of the epiglottis and the PES. 23 In elderly patients over 65 years old specifically, Chiesa Estomba et al reported postoperative rates of aspiration pneumonia of 20% after open surgery and of 41.2% after TLM in supraglottic carcinoma, albeit difference was not statistically significant and the rates of dysphagia were similar, 30% versus 29.4%, respectively. 9 Together with our results, these findings argue for considering a transoral procedure rather than an open procedure for a tumor smaller than thirty millimeters when local exposition is favorable and no local extension associated with a risk of decreased local control after a transoral is suspected.…”
Section: Discussionmentioning
confidence: 97%
“…Although TLM has been reported to be associated with similar survival in intermediate‐size tumors, our local preferences for OPHL type I were based on the goals of optimizing local control and laryngeal preservation 21,22 . Regarding functional outcomes, Bertolin et al, found worse results in patients undergoing endoscopic epiglottis and PES resection compared to patients undergoing the same resection by open approach reported to the increase in the sphincter capacity potentially obtained by a compensatory effect of the laryngopexy performed in open surgery, advocating for the authors for open surgery in every case requiring resection of the epiglottis and the PES 23 . In elderly patients over 65 years old specifically, Chiesa Estomba et al reported postoperative rates of aspiration pneumonia of 20% after open surgery and of 41.2% after TLM in supraglottic carcinoma, albeit difference was not statistically significant and the rates of dysphagia were similar, 30% versus 29.4%, respectively 9 .…”
Section: Discussionmentioning
confidence: 99%
“…ESL generally allows for shorter time for swallowing recovery, reduced tracheostomy maintenance, and lower incidence of aspiration pneumonia ( 18 ) because of the complete preservation of the sensation of the vestibule and hypopharynx by sparing the superior laryngeal nerve in the majority of the cases, of the accessory muscles that normally contribute to the craniocaudal movements of the larynx, and of an effective cough reflex that may prevent severe problems ( 4 , 23 , 24 ). However, major dysfunction after ESL, such as permanent tracheostomy and/or PEG, have been reported in the literature (Table 7 ) ( 1 , 5 , 6 , 14 , 25 , 26 ). In the present series, we did not perform any PEG, and all tracheostomies were removed within 1 month from surgery.…”
Section: Discussionmentioning
confidence: 99%